Nephtys pente sp. nov. (Polychaeta: Nephtyidae) and a Key to Nephtys from Northern Europe - Rainer, Sebastian F. (Journal of the Marine Biological Association of the United Kingdom, 1984)
Nephtys pente sp.nov. is described. The species is known to occur in shallow waters from the western Baltic to Greenland. It may occur with Nephtys ciliata, which it closely resembles. An amended definition for N. ciliata is proposed. A key is provided for the northern European species of Nephtys.
World Polychaeta Database (WPolyDb)